Creations de UiTM 2020 Proceeding Book - UiTM, Pusat Asasi (Pusat Asasi, UiTM Cawangan Dengkil, 2020)
CREATIONS de UiTM: Mega Innovation Carnival 2020 is one of Centre of Foundation Studies UiTM Kampus Dengkil’s very own national level innovation competition & exhibition that showcases creativity and innovation skills among students. There were over 100 competing innovation projects from Malaysian pre university and secondary school students as well as over 100 Asasi UiTM students’ innovation project showcases. There were two categories of competition which were Category A: Pre-University, and Category B: Secondary School. There were various awards to be won; Diamond, Gold, Silver, and Bronze for both categories.